Two new species and one new record of the genus Asprothrips (Thysanoptera: Thripidae) from China - Tong, Xiaoli; Wang, Zhaohong; Mirab-Balou, Majid (Zootaxa, 2016)
Two new species of the genus Asprothrips Crawford, A. bucerus sp. n. and A. punctulosus sp. n. are described and illustrated from China. A. bimaculatus Michel & Ryckewaert, previously known only from Martinique in the French West Indies and Malaysia, is newly recorded from mainland China and Taiwan, along with the first descriptive notes of the male, and the record from China of A. fuscipennis Kudô is considered a misidentification of A. bucerus sp. n. The generic diagnosis of Asprothrips is briefly summarized and an updated key to world species of the genus is also presented.